Experimental investigation of the hydraulic and heat-transfer properties of artificially fractured granite - Luo, Jin; Zhu, Yongqiang; Guo, Qinghai; Tan, Long; Zhuang, Yaqin; Liu, Mingliang; Zhang, Canhai; Xiang, Wei; Rohn, Joachim (Scientific Reports, 2017)
In this paper, the hydraulic and heat-transfer properties of two sets of artificially fractured granite samples are investigated. First, the morphological information is determined using 3D modelling technology. The area ratio is used to describe the roughness of the fracture surface. Second, the hydraulic properties of fractured granite are tested by exposing samples to different confining pressures and temperatures. The results show that the hydraulic properties of the fractures are affected mainly by the area ratio, with a larger area ratio producing a larger fracture aperture and higher hydraulic conductivity. Both the hydraulic apertureand the hydraulic conductivity decrease with an increase in the confining pressure. Furthermore, the fracture aperture decreases with increasing rock temperature, but the hydraulic conductivity increases owing to a reduction of the viscosity of the fluid flowing through. Finally, the heat-transfer efficiency of the samples under coupled hydro-thermal-mechanical conditions is analysed and discussed. © The Author(s) 2017.